2020
DOI: 10.2147/rru.s259941
|View full text |Cite
|
Sign up to set email alerts
|

<p>X-ray-free Ultrasound-guided Percutaneous Nephrolithotomy in Supine Position Using Alken Metal Telescoping Dilators in a Large Kidney Stone: A Case Report</p>

Abstract: X-ray-free ultrasound-guided percutaneous nephrolithotomy (PCNL) has been proven to be safe, feasible, and affordable. Kidney dilatation during X-ray-free ultrasound-guided PCNL is mostly using balloon dilators. This report presents our experience of performing X-rayfree ultrasound-guided PCNL in supine position using Alken metal telescopic dilators in a patient with a large kidney stone. A 50-year-old male presented with right complete staghorn stone sized 46×30×24 mm (stone burden: 50,985 mm 3 with sphere fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…All but those who had complications, recovered uneventfully. Another study showed that complications rate is lower in supine group that is statistically significant 13 .…”
Section: Original Articlementioning
confidence: 89%
“…All but those who had complications, recovered uneventfully. Another study showed that complications rate is lower in supine group that is statistically significant 13 .…”
Section: Original Articlementioning
confidence: 89%
“…We have reported our experience of performing this X-ray free procedure in PCNL previously. 7 , 8 The aim of this report is to present our first-hand experience of performing X-ray-free ECIRS in a case of complex ureteral stone. To our knowledge, this is the first report of such a case.…”
Section: Introductionmentioning
confidence: 99%